ANALISIS PEMBIASAAN NILAI - NILAI AKHLAKUL KARIMAH SEBAGAI UPAYA PEMBANGUNAN KARAKTER PADA ANAK USIA DINI DI DAERAH TERDEPAN, TERLUAR DAN TERTINGGAL (3T) KABUPATEN ROTE NDAO - Winnuly, Winnuly; Munawaroh, Mufidatul; Hidayah, Siti Fatimah Nur (Universitas Islam Darul Ulum, 2024)
The phenomenon of a character crisis resulting in moral decline in the nation's generation should be overcome through the role of education as an effort to familiarize oneself with moral values. Schools and teachers have an important role in forming children's morals apart from family and parents in educating them, especially during the learning process. Facilitating the akhlakul karimah (noble character) needs of children in underdeveloped, outermost and frontier areas is an important and urgent challenge. This research uses a qualitative descriptive research approach. The aim of this research is to collect as much factual data as possible on the subject naturally in implementing the practice of akhlakul karimah values as an effort to build character in early childhood in frontier, outermost and disadvantaged areas (3T). Efforts to facilitate children's moral and moral needs are often not a top priority. Nevertheless, the importance of character and morality formation in children should not be ignored. To overcome this challenge, a collaborative approach between various parties, inclusive education that integrates moral values in educational programs, parent training, use of technology, community strengthening, and social skills development programs can be an effective solution.